About Linguistic Units in Bilingual Speech (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
One of the interesting and relevant issues for linguistics related to the problem of "language and society" seems to us the question of bilingualism, and where, like nowhere else, the influence of social conditions on the development of the language is manifested. It is here, in bilingualism that the linguistic and sociological approaches to language learning organically merge into one inseparable whole - into a kind of dual unity. And this dual unity is strictly necessary here, because bilingualism, or bilingualism, is a linguistic object in its material and an object of sociology for internal reasons for the emergence and functioning in society. In other words, the linguistic and sociological moments in bilingualism are closely connected and interdependent, but at the same time it is indisputable that social, specifically historical reasons always lie at the heart of bilingualism. There is no need to prove that the study of specific forms and types of bilingualism has political, linguo-theoretical and practical significance for us. Bilingualism or multilingualism is a very common phenomenon.